2010
DOI: 10.1016/j.wocn.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the spectral distinction between sibilant fricatives through a speaker-centered approach

Abstract: This study was designed to examine the feasibility of using the spectral mean and/or spectral skewness to distinguish between alveolar and palato-alveolar fricatives produced by individual adult speakers of English. Five male and five female speaker participants produced 100 CVC words with an initial consonant /s/ or /ʃ/. The spectral mean and skewness were derived every 10 milliseconds throughout the fricative segments and plotted for all productions. Distinctions were examined for each speaker through visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 19 publications
5
15
0
5
Order By: Relevance
“…When estimated from either the beginning, middle, or end of the fricative noise, centroid frequency has been found to be greater in /s/ than in /S/ (Jongman et al, 2000), and similar results have been found when centroid frequency measurements from multiple locations across the fricative are pooled together Maniwa et al, 2009). In each of these studies, the difference in centroid frequency was evaluated across a group of talkers, and when the perspective shifts to the individual talker, the same pattern obtains (Haley et al, 2010;Li et al, 2009). As is the case with centroid frequency, peak frequency has been found to be higher in /s/ than in /S/, regardless of whether it is measured at the beginning, middle, or end of frication (Behrens and Blumstein, 1988;Heinz and Stevens, 1961;Hughes and Halle, 1956).…”
Section: Introductionmentioning
confidence: 59%
“…When estimated from either the beginning, middle, or end of the fricative noise, centroid frequency has been found to be greater in /s/ than in /S/ (Jongman et al, 2000), and similar results have been found when centroid frequency measurements from multiple locations across the fricative are pooled together Maniwa et al, 2009). In each of these studies, the difference in centroid frequency was evaluated across a group of talkers, and when the perspective shifts to the individual talker, the same pattern obtains (Haley et al, 2010;Li et al, 2009). As is the case with centroid frequency, peak frequency has been found to be higher in /s/ than in /S/, regardless of whether it is measured at the beginning, middle, or end of frication (Behrens and Blumstein, 1988;Heinz and Stevens, 1961;Hughes and Halle, 1956).…”
Section: Introductionmentioning
confidence: 59%
“…A discrete cosine transformation (DCT) was then applied to each speaker-normalized M 1 trajectory. The reason for representing M 1 trajectories with DCT coefficients is because of the evidence that sibilants in different contexts vary not just at the target but also dynamically (Haley et al 2010;Iskarous, Shadle, & Proctor 2011;Koenig et al 2013). The first three DCT coefficients are proportional respectively to the mean, linear slope, and curvature of the trajectory and thereby encode dynamic information between the acoustic onset and offset of each (speaker-normalised) M 1 trajectory (Watson & Harrington 1999).…”
Section: Acoustic Parametersmentioning
confidence: 99%
“…В отличие от многих типов звуков для сибилянтов чрезвычайно трудно выделить такие акустические параметры, которые надежно отличали бы их друг от друга на уровне языка [Newman et al, 2001;Haley et al, 2010]. Кроме того, иногда сделать обобщения о качестве s в языке оказывается невозможным, потому что данные носителей слишком различаются [Gordon et al, 2002].…”
Section: вариативностьunclassified
“…В лингвистической среде даже возникло мнение, что для сибилянтов вовсе невозможно выделить акустический инвариант, а есть только относительное расположение на спектральной картине (см. обзор: [Haley et al, 2010]).…”
Section: вариативностьunclassified